The role of tax system complexities in shaping decision-making processes of small and medium enterprises: evidence from Laghouat, Algeria - Zemmit, Zeyneb (The International tax journal, 2025)
This paper aims to analyse the role of tax system complexities in Algeria on small and medium enterprises (SMEs), specifically regarding their operational, investment, and financial decisions. To achieve this, a descriptive-analytical methodology was employed, utilising a questionnaire distributed to a randomly selected sample of 52 SMEs operating in Laghouat. The study found that tax system complexities play a significant role in shaping SME decisions overall, with particular influence on investment and financing decisions.